SUSTAINABILITY AND HUMAN DEVELOPMENT: A PROPOSAL FOR A SUSTAINABILITY ADJUSTED HUMAN DEVELOPMENT INDEX - PINEDA, José (Theoretical and Practical Research in Economic Fields, 2012)
This paper proposes sustainability - adjusted human development index (SHDI) in which countries’ achievements in human development are penalized if there is over-exploitation of the environment. The human development approach has been a powerful framework in the past for advancing the measurement of human progress, particularly the human development index (HDI), which is a capabilities index aiming to capture to what extent people have the freedom to live substantively different lives. Today, this approach can help us make more explicit the profound connections between current and future generations’ choices by offering a framework for understanding sustainability that connects inter- and intra-generational equity with global justice. The empirical analysis shows that there are important global sustainability challenges ahead since there are 90 (out of 185) countries with per capita CO 2 emissions above the planetary boundaries. There are 19 countries that lose at least one position in their HDI ranking after adjusting for sustainability. Between these countries, however, the countries that experienced the largest drop in ranking were 102 positions for the United States, 39 positions for China, and 22 positions for the Russian Federation.